Pembelajaran Berbasis Proyek Untuk Meningkatkan Logika Dan Kemampuan Pengambilan Keputusan Pada Siswa Sekolah Dasar (Tinjauan Studi Literatur): Project-Based Learning to Improve Logic and Decision-Making Skills in Elementary School Students (A Literature Review) - Asti Hardianti; Eva Yuliawati; Siti Nur Syamsiah (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study aims to assess the effectiveness of project-based learning (PjBL) methods in improving the logic and decision-making skills of elementary school students. Using literature studies, an analysis was conducted on many relevant studies to understand the impact of PjBL in the educational context. The findings indicate that PjBL is effective in developing logical thinking and decision-making skills through solving real problems. This approach emphasizes collaboration, active exploration, and student involvement in projects that are relevant to everyday life. In addition to strengthening analytical and critical thinking skills, PjBL also encourages independent learning and teamwork, making it a suitable method for the needs of modern education.